Validation of the Thai translation of the attitudes toward euthanasia scale - Metha Trikasemmart; Pichayathida Siriwechdaruk; Pavitra Hsieh; Pornpailin Paradeevissut; Napassorn Wongakkarakhun; Smith Srisont; Pawin Numthavaj; Wisarn Worasuwannarak (Heliyon)
In Thailand, euthanasia has been a controversial topic for several decades. The assessment of attitudes toward euthanasia among medical students who will become future medical practitioners is essential for the progression of future legislation and practice. This study aimed to adapt and validate the Attitude Towards Euthanasia scale in the Thai context and measure its validity and reliability. First, the scale was translated into Thai by certified translation centers using the forward-backward technique. This cross-sectional study involved 112 Thai students. Self-reported online questionnaires and the Attitude Towards Euthanasia scale were used for data collection. The psychometric properties of the scale were analyzed using internal consistency (Cronbach's alpha and McDonald's Omega coefficient), reproducibility, exploratory factor analysis, and confirmatory factor analysis. Cronbach's alpha for the Thai Attitude Towards Euthanasia scale was 0.83, and the reproducibility was acceptable, with no statistically significant difference between the first and subsequent responses for each item. The two-factor model was extracted using exploratory factor analysis, and the values of the Kaiser-Meyer-Olkin criterion and Bartlett's test of sphericity all fell within a satisfactory range. Two- and four-factor models were analyzed for the confirmatory factor analysis, and the latter provided more acceptable model fit indices. In conclusion, the Thai Attitude Towards Euthanasia scale is valid for assessing attitudes toward euthanasia among Thai medical students.